HGG-17. TUMOR MUTATIONAL BURDEN ANALYSIS OF PEDIATRIC TUMORS PROVIDES A DIAGNOSTIC TOOL FOR GERMLINE REPLICATION REPAIR DEFICIENCY AND PREDICT RESPONSE TO IMMUNE CHECKPOINT INHIBITION. Issue 2 (22nd June 2018) - Campbell, Brittany B; Light, Nicholas; Fabrizio, David; Bouffet, Eric; Larouche, Valerie; Samuel, David; Stearns, Duncan; Cole, Kristina A; Opocher, Enrico; Thomas, Gregory; Sabel, Magnus; Dirks, Peter; et al.
Abstract: BACKGROUND: Hypermutation constitute an important subgroup of cancers and confers sensitivity to immune checkpoint inhibition (ICI). Glioblastoma arising in children with Constitutional Mismatch Repair Deficiency Syndrome (CMMRD) are ultrahypermutant. Our objective was to quantify the frequency of hypermutant tumors in children, determine whether mutational signatures can predict germline mutations, and treat hypermutant tumors with ICIs. METHODS: Deep panel sequencing of 2984 pediatric tumors (585 brain tumors). Tumor mutation burden was correlated to mutation burden from exome and genome sequencing (R 2 = 0.94). Mutational signatures were analyzed to predict source of hypermutation. Data on 36 patients with hypermutant tumors identified by sequencing were enrolled on an ICI registry trial. RESULTS: Hypermutant tumors (>10 mut/MB) comprised 5% of all pediatric tumors (n=143). These were highly enriched for replication repair mutations (p<0.0001) and mutation loads correlated with hypermutant adult tumors that have shown demonstrable clinical response to ICI. Hypermutation was found in 5% of childhood and 6% of adult glioblastoma. All glioblastomas with greater than 100 Mut/MB harbored MMR/polymerase mutations suggesting germline bMMRD (p =10 -7 ). Clinical data collected on 19 ultrahypermutant tumors revealed germline mutations in replication repair genes in all patients. Of the 36 patients with hypermutant cancers treated with ICI, 24 had brain tumors, and favorable sustained responses are observed. CONCLUSION: High mutation burden is a sensitive predictor of germline CMMRD. Hypermutant tumors are more common in the pediatric setting than previously appreciated, opening novel therapeutic avenues. ICI shows promise for hypermutant pediatric cancers including glioblastoma.